(untitled) (TAJ: Journal of Teachers Association, 2020)
Pediatric urinary tract infections (UTI) are associated with significant morbidity and potential long term complication like extensive renal scarring leading to end stage renal disease. Prompt diagnosis and early initiation of treatment is necessary to prevent long term complications. Knowledge about bacteriological profile of pediatric urinary tract infections and their antimicrobial sensitivity pattern is helpful for initiation of empirical antibiotic treatment. The aim of this study was to identify the causative bacteria and antimicrobial sensitivity pattern of community acquired UTI in children attending outpatient department of a tertiary level hospital of Bangladesh. This was a cross-sectional study conducted in pediatric outpatient department of Rajshahi Medical College Hospital, Bangladesh over 6 month period from 1st January 2017 to 30th June 2017. Children aged < 12 year who presented with clinical features suggestive of urinary tract infection were subjected for urinary routine and microscopic examination and culture. Colony counts of the culture positive cases were done and antibiotic sensitivity and resistance patterns were studied. Samples with colony count of ≥ 105 CFU/ml were considered significant. Among the 134 clinically suspected cases significant bacteriuria was found in 81 (60.45%) children. Escherichia coli was the most common isolate (74.1%) followed by Proteus (9.8%), Klebsiella spp. (8.6%), Pseudomonas (6.2%) and Staphylococcus saprophyticus (1.2%). E. coli was found to be highly sensitive to imipenem, amikacin, nitrofurantoin and ciprofloxacin. Klebsiella showed good sensitivity against ciprofloxacin and imipenem whereas proteus, Pseudomonas and Staphylococcus saprophyticus showed sensitivity against imipenem, amikacin and ciprofloxacin. Increased resistance was noted against the commonly used empirical antibiotics such as cephradin, cefuroxime, cefixime, ceftriaxone and co-trimoxazole. Therefore, selection of empirical therapy should be based on local bacteriological profile and their antimicrobial sensitivity pattern. TAJ 2020; 33(2): 27-31